2023
DOI: 10.1002/nau.25138
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment does not impact sacral neuromodulation implant rates for overactive bladder

Abstract: Objective To evaluate the impact of cognitive impairment (CI) diagnoses on sacral neuromodulation (SNM) outcomes in older patients. Materials and Methods We completed a retrospective review of all patients aged ≥55 years who underwent test‐phase SNM (peripheral nerve evaluation (PNE) or stage 1) for overactive bladder (OAB) between 2014 and 2021 within a large multi‐regional health system. Patient demographics, relevant comorbidities, CI diagnoses (dementia or mild CI), and SNM procedures were recorded. Logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Zillioux et al , in a retrospective analysis of patients who underwent SNM for OAB found 10.2% (52/510) had cognitive impairment diagnosis in their chart at time of test-phase implant, with an additional 6% (30/510) receiving a diagnosis following test-phase SNM ( 65 ). Based on the retrospective methods which relied on electronic medical record diagnosis codes, the authors noted that these estimates were likely an underestimate.…”
Section: Discussionmentioning
confidence: 99%
“…Zillioux et al , in a retrospective analysis of patients who underwent SNM for OAB found 10.2% (52/510) had cognitive impairment diagnosis in their chart at time of test-phase implant, with an additional 6% (30/510) receiving a diagnosis following test-phase SNM ( 65 ). Based on the retrospective methods which relied on electronic medical record diagnosis codes, the authors noted that these estimates were likely an underestimate.…”
Section: Discussionmentioning
confidence: 99%
“…While impaired cognition could certainly affect a patient's ability to make adjustments in therapy after permanent implantation, which may limit the efficacy of the device, more importantly it could affect the ability of the provider to assess the efficacy during trial phase if the patient is unable to clearly articulate improvements. However, a recent retrospective review on the use of SNM in people over 55 years old found that a pre-existing diagnosis of cognitive impairment was not a predictor in going on to final implantation of the device, suggesting cognitive impairment should not exclude the use of this therapy in older patients [92]. Finally, implantation of the device is also more invasive than other third-line OAB treatments, and the risk of undergoing even this minor surgical procedure in a frail patient should be considered carefully.…”
Section: Third-line Treatments For Overactive Bladdermentioning
confidence: 99%